Proactive community support tailored to holistic needs: A cohort study - Austyn Snowden; Jenny Young; Jan Savinc (Cancer Medicine)
Abstract Background It is increasingly internationally recognized that a cancer diagnosis impacts on people practically and financially as well as physically and psychologically. It is less clear what to do about this. This study introduces an original community service designed to mitigate this wider impact. Nonclinical “link officers” use holistic needs assessment (HNA) to help newly diagnosed people identify and quantify the severity of their physical, psychological, practical, financial, and social concerns. A care plan is then agreed, usually involving community interventions from partner agencies. Following intervention, assessment is repeated. The primary aim of this study was to establish whether there was a significant difference between initial assessment and follow‐up, postintervention. Secondary aim was to identify potential predictors of increased levels of concern at baseline and follow‐up. Method Pre‐ and postintervention observational cohort study. Paired t test examined the difference in mean (SD) concern severity between baseline and follow‐up. Multiple linear regression models were computed to hypothesize potential predictors of initial concern severity and severity change. Results The service saw 2413 people 2014‐2017. Participants identified average 5.5 (4.7) concerns, financial concerns being most frequent. Mean severity at baseline was 7.12 (out of 10) (2.50), reducing to 3.83 (3.49) post‐treatment, paired t(4454) = 64.68, P < 0.0001, reduction of 3.31 (95% CI 3.21‐3.41). Factors associated with higher initial concern included unemployment and caring responsibilities. Unemployment was also associated with a smaller reduction of concern severity at follow‐up. Conclusion Patient level of concern went from a level associated with specialist referral to a much more manageable level. This original finding is internationally significant because it extends Khera et al's (2017) “provocative idea” that all patients should be screened for financial problems to show that they can be helped with all their concerns. This article describes a successful, transferable model of community care.